What is an ecosystem to the material and the maker? : a thesis presented in partial fulfilment of the requirements for a Master of Design at Massey University, Wellington, New Zealand - Rae, Genevieve (Massey University, 2023)
Right now, the human-material relationship is strained, misunderstood, and destructive. This exegesis explores some of Aotearoa’s human-material relationships and develops tools to design with in response. Through a multispecies philosophy lens, I investigate how designers might reposition themselves by considering materials design beyond human use in order to design more holistically. The project explores the creation of mycelium based materials and a practice of weaving in wild ecosystems. I will discuss systems that govern our human-nature relationships, the aspirations we have to achieve a circular economy, and aspects of well being that are woven into our environmental relations. Designers, across specialisation and disciplines, build our world, our physical and experiential surroundings. In order to do this ethically, as the custodial species, designers must listen to the terms set out by the land we design on and the ecosystems we design for. The outcomes of this project are offerings of tools and processes for approaching co-design with non-human organisms for the intention of designing in symbiosis with local ecosystems. This exegesis outlines my journey of making and unmaking with care and consideration for the inhabitants who share this place with us.
Keywords: 330304 Design history, theory and criticism